Frictional Resistance Increase Due to Hull Roughness: An Analysis of the Hull Form Parameters Influence - Hakim, Muhammad Luqman; Suastika, I Ketut; Utama, I Ketut Aria Pria; Purnamasari, Dian; Muryadin, Muryadin (Transactions on Maritime Science, 2023)
An awareness of the drag increase brought on by biofouling's roughness on the ship hull is one technique to cut emissions aboard ship. However, predicting the increased drag on ships poses significant challenges. When predicting the rise in frictional resistance brought on by roughness, the hull is considered flat. In fact, ship hulls have a variety of shapes, and it is not certain whether this is a factor influencing the magnitude of the increase in resistance due to roughness. In this article, the effect of the hull's form parameters— (ratio of length per breadth), (coefficient block), and (Length of center buoyancy)—on the increase in frictional resistance brought on by roughness have been investigated. The method used to calculate the ship resistance is Computational Fluid Dynamics (CFD) simulation, complemented by roughness modelling using the wall function approach method. The Design of Experiment (DOE) method has been used to vary the shape of the hull model as a variation of the test specimen in this study. The verification and validation tests have been carried out on the CFD simulation results, where the results have been compared with proven empirical methods. Based on the study results, the value of frictional resistance and increased frictional resistance () of all specimens has shown no significant difference in value, evidenced by the variance values, ranging only 1.57-2.1%. Thus, these results prove that the increase in frictional resistance due to roughness is sufficient to assume the ship's hull as a flat plate. The other finding is that roughness can also increase the pressure resistance, and hull shape parameters also contribute towards changes in the value of resistance.